2013
DOI: 10.1002/adsc.201201033
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Domino SN2′/Coupling Reaction: A Versatile and Facile Synthesis of Cyclic Compounds from Baylis–Hillman Acetates

Abstract: A variety of substituted quinoline/pyridine, thiochromene and naphthalene derivatives, which might be of biological and medicinal value, were synthesized by copper-catalyzed domino S N 2'/coupling, S N 2'/deacylation/coupling and S N 2'/coupling/elimination reactions. The method provides a general and convenient approach to the synthesis of various sub-stituted cyclic compounds from the corresponding Baylis-Hillman (B-H) acetates and N-/S-/C-nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…We began our studies with MBH acetate 1a by using our previously reported conditions (Scheme ). [6b] Initially, reaction of 1a (0.5 mmol) with methyl acetoacetate (1.5 equiv.) was performed by using K 2 CO 3 (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We began our studies with MBH acetate 1a by using our previously reported conditions (Scheme ). [6b] Initially, reaction of 1a (0.5 mmol) with methyl acetoacetate (1.5 equiv.) was performed by using K 2 CO 3 (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…They are highly versatile reagents in synthetic organic chemistry because of their easy conversion into the corresponding enolates They have been employed in a variety of reactions such as condensation, alkylation, cyclization halogenation, acylation, and Michael addition . Recently, their cascade reaction with Morita–Baylis–Hillman (MBH) acetates through successive S N 2′–S N Ar and eliminative aromatization was reported for the synthesis of naphthalene and quinoline derivatives (Figure ) . We also reported the synthesis of acridine[6b] by using malononitrile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a one-pot approach to indolo[1,2-f]-phenanthridines from o-alkynylanilines and 1,2-dihaloarenes has not been achieved until now. As part of our ongoing research efforts toward the domino synthesis of heterocycles under copper catalysis, 27,[37][38][39][40] we became interested in applying the one-pot protocol to the assembly of 1,2-disubstituted indoles and the tandem synthesis of indolo[1,2-f]phenanthridines. The findings are reported herein.…”
Section: Methodsmentioning
confidence: 99%